Extracorporeal blood purification in the complex treatment of the novel coronavirus infection: the review of opportunities - A. A. Sokolov; D. V. Sokolov; D. V. Pevzner; A. V. Popov; V. V. Donskikh (Вестник анестезиологии и реаниматологии)
The objective: to provide pathogenetic justification for the need for extracorporeal blood purification in the new coronavirus infection.Results: the article analyzes guidelines and the first experience of using extracorporeal methods in the new coronavirus infection in different countries. It has been demonstrated that methods of extracorporeal blood purification have complex pleiotropic (multiple) effects and can quickly normalize the level of cytokines and other pathogenic factors, thereby preventing/reducing the severity of organ disorders. The article specifies the criteria for choosing an extracorporeal method, as well as indications for its early and late use.